8-6m=3m-1

Simple and best practice solution for 8-6m=3m-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-6m=3m-1 equation:


Simplifying
8 + -6m = 3m + -1

Reorder the terms:
8 + -6m = -1 + 3m

Solving
8 + -6m = -1 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
8 + -6m + -3m = -1 + 3m + -3m

Combine like terms: -6m + -3m = -9m
8 + -9m = -1 + 3m + -3m

Combine like terms: 3m + -3m = 0
8 + -9m = -1 + 0
8 + -9m = -1

Add '-8' to each side of the equation.
8 + -8 + -9m = -1 + -8

Combine like terms: 8 + -8 = 0
0 + -9m = -1 + -8
-9m = -1 + -8

Combine like terms: -1 + -8 = -9
-9m = -9

Divide each side by '-9'.
m = 1

Simplifying
m = 1

See similar equations:

| y^3z+y^2z^2-5y^2z-5yz^2= | | (4n+1)=12 | | (-a+3)=-2(2a+1)-7 | | -4(-7x+1)+5(8-4x)=-4 | | 3(y+1)=4 | | 7x^2+3x-54=0 | | 18x^2+2x-0.07=0 | | 3x^2-7x-1.25=0 | | 543x+22=346 | | 8x-3=6x-5 | | 6k-4k=4 | | 3x+30y=2 | | x*x=18 | | 8x^2=4-2x | | 5(x-5)+7=3(x-4) | | (x-2)(x-2)-4-21=0 | | 6x-4y-1=0 | | 7-3(a+2)=9+a | | 0.1(x+20)+1.7x=83 | | I=g+4gh | | 14+3y=20 | | -4x+6=-2(4x+15) | | 7a+3+(-9-5)=-16 | | x*x-18=0 | | 11-4k= | | 9(x-4)-4=-40 | | 25-6x=14x | | 7-7x-3=-48+4x-14 | | 0.4(x-2)=6.4 | | [4+6r]=26 | | 24-2x=180 | | x+1/4=3/5 |

Equations solver categories